Developmental partitioning of SYK and ZAP70 prevents autoimmunity and cancer - Sadras, Teresa (Mol Cell, 2021)
Even though SYK and ZAP70 kinases share high sequence homology and serve analogous functions, their expression in B- and T-cells is strictly segregated throughout evolution. Here, we identified aberrant ZAP70-expression as a common feature in a broad range of B-cell malignancies. We validated SYK as the kinase that sets the thresholds for negative selection of autoreactive and premalignant clones. When aberrantly expressed in B-cells, ZAP70 competes with SYK at the BCR-signalosome and redirects SYK from negative selection to tonic PI3K signaling, thereby promoting B-cell survival. In genetic mouse models for B-ALL and B-CLL, conditional expression of Zap70 accelerated disease onset, while genetic deletion impaired malignant transformation. Inducible activation of Zap70 during B-cell development compromised negative selection of autoreactive B-cells, resulting in pervasive autoantibody production. Strict segregation of the two kinases is critical for normal B-cell selection and represents a central safeguard against the development of autoimmune disease and B-cell malignancies.